Metaphors of Change: Navigating a Revolution in Engineering Education. Issue 1 (2nd January 2021) - Breslin, Samantha; Camacho, Michelle M.
ABSTRACT: Engineering education is often decontextualized, even as it is suffused with metaphoric language and sociocultural norms and beliefs. Efforts to embed social context and sociotechnical content in engineering education are often met with resistance. We contribute to conversations about how to change dominant knowledge regimes by detailing the process by which a team grapples with efforts to change technically-focused curricula and practices in engineering education – and faculty members' values and beliefs about them – by invoking metaphors. Metaphors of war and revolution, conversion/evangelism, and care permeate faculty discourse as they interpret and attempt to enact change. We show how these metaphors are significant in the ways that they both enable and constrain possibilities for change.